ANALISIS PELUANG PENGEMBANGAN INDUSTRI GULA AREN DALAM MENDUKUNG SWASEMBADA GULA NASIONAL - Ir. H. Dian Kusumanto (Jurnal Pertanian Tropik, 2016)
This study aims to provide a critical and in-depth analysis of the Arenga palm sugar industry development opportunities in support of national self-sufficiency in sugar, as long as the self-sufficiency program in Indonesia only rely on cane-based sugar industry. Failure of sugar self-sufficiency efforts so far indicate that sugar cane-based industry is need for the development of alternatives to meet the national sugar needs. Efforts to increase sugarcane production is constrained by the difficulty of developing a planting area, declining soil fertility and productivity of sugarcane. Refiners are already very old age is also not able to be replaced with a new sugar plant that requires very large investments. This situation led to inefficiencies and yield of sugar cane harvest has declined. In addition, there are great opportunities Arenga plant which has many advantages compared to cane as raw material for sugar industry. However, the development of the sugar industry based Arenga requires government policies that encourage the availability of information, science and latest technology of Arenga, incentives for investors in the form of ease of licensing and the provision of land, concerns about the proliferation of liquor is also to be anticipated by the legislation, monitoring and enforcement. Alternative policy is believed will give great confidence in supporting national self-sufficiency in sugar, also confirmed to the welfare of its players. Then advised all parties to take on the role in order to meet Arenga presence as supporting sugar self-sufficiency in Indonesia.